2018
DOI: 10.1097/md.0000000000012611
|View full text |Cite
|
Sign up to set email alerts
|

Raman characterizations of red blood cells with β-thalassemia using laser tweezers Raman spectroscopy

Abstract: This study aimed to study the differences in Raman spectra of red blood cells (RBCs) among patients with β-thalassemia and controls using laser tweezers Raman spectroscopy (LTRS) system.A total of 33 patients with β-thalassemia major, 49 with β-thalassemia minor, and 65 controls were studied. Raman spectra of RBCs for each sample were recorded. Principal component analysis (PCA), one-way analysis of variance (ANOVA), and independent-sample t test were performed.The intensities of Raman spectra of β-thalassemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Therefore, it would be interesting to carry out another type of assay, referred to as the immuno-labeling of the cell membrane, which can only be carried out with the cells fixated; this would be helpful for detecting affectations in the structure of the cell membrane, which are not currently clearly determined. Nevertheless, another advantage of the combined use of the imaging techniques described in this work, unlike other classical tests (such as complete blood count, blood smears, or electrophoresis), is that it does not necessarily require reactives or the use of markers and fixating substances used to capture absorption spectra [30]. Thus, tests can be carried out in normal physiological conditions without the need to prepare hemolyzed serums and with a relatively low volume of RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be interesting to carry out another type of assay, referred to as the immuno-labeling of the cell membrane, which can only be carried out with the cells fixated; this would be helpful for detecting affectations in the structure of the cell membrane, which are not currently clearly determined. Nevertheless, another advantage of the combined use of the imaging techniques described in this work, unlike other classical tests (such as complete blood count, blood smears, or electrophoresis), is that it does not necessarily require reactives or the use of markers and fixating substances used to capture absorption spectra [30]. Thus, tests can be carried out in normal physiological conditions without the need to prepare hemolyzed serums and with a relatively low volume of RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Jia W. in 2018 was study the differences in Raman spectra of red blood cells (RBCs) among patients with β-thalassemia using PCA [20]. MU Ali in 2017 reported that Bioinformatics data is high dimensional, so that using PCA to selected of attributes of data for getting accurate results in classification, Prediction, Clustering and Pattern Extraction are useful techniques of data mining [21]. Sharma in 2012 was reported that there are no literatures yet with regard to the anemic RBCs feature selection that has been published [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This spectroscopic tool have found high potential in health sciences for diagnosing cell abnormalities by probing the dynamic cellular processes at single cell level [20,21]. Researchers have already combined optical tweezers and Raman spectroscopy to gather vital information regarding the biochemical alterations occurring in a single biological cell to investigate various disease conditions [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%